The Effect of Implementing Authentic Assessment on Student Learning Activities and Outcomes - Lestari, Lestari (Program Magister Teknologi Pendidikan Universitas Jambi, 2021)
This study investigates the effect of implementing authentic assessment on student learning activities and outcomes in the context of elementary school history education. The research design involved an experimental approach, with one group receiving authentic assessment and another group receiving conventional assessment. Participants were fifth-grade students from a specific school. Data collection methods included pre-test and post-test assessments, observation of student activities during lessons, and a questionnaire to gauge student attitudes toward the learning process. The findings revealed that students who underwent authentic assessment demonstrated higher levels of engagement in learning activities compared to those subjected to conventional assessment. Additionally, significant improvements were observed in the learning outcomes of students in the authentic assessment group. This suggests that authentic assessment not only fosters greater student involvement in the learning process but also enhances their understanding and retention of the subject matter. These results underscore the importance of incorporating authentic assessment practices in educational settings to promote more meaningful and effective learning experiences for students.